TINJAUAN YURIDIS KEWENANGAN MENTERI KEUANGAN DALAM MEMPAILITKAN BADAN USAHA MILIK NEGARA (BUMN) - , hendry septiawan ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research is aimed at analyzing the provision of an authority for the Minister of Finance to file bankruptcy against the State-Owned Enterprises (SOEs) and analyzing the types of SOEs against which the Minister of Finance can file a bankruptcy petition. It belongs to a normative legal research done by examining library materials or secondary data consisting of primary law materials, secondary law materials and tertiary law materials. Data were collected using a method of documentation and a tool of documentary study. Subsequently, they were analyzed qualitatively. The results and discussion of research indicated that the Minister of Finance is the only party that entitled to file a bankruptcy petition against the SOEs for the public benefit purposes because the regulators found the Minister of Finance has abundant and profound information about the SOEs. Therefore, when there is a bankruptcy petition, the minister can make a right decision. In regard to the types of SOEs, it should be SOEs established in the form of public enterprises and engaged for the public benefits whose capital is entirely owned by the state and is not divided into shares. Article 1 (4) of the Law concerning SOEs clearly defines that a public enterprise is SOE whose entire capital is owned by the state and not divided into shares for the public benefit purposes and in the pursuit of profits. It can be conclude that the Minister of Finance is authorized to file a bankruptcy of SOEs engaged for the public benefits because it is the most party that understand the financial condition of the SOEs and is able to estimate the consequences. The types of SOEs that can be bankrupted by the Minister of Finance are SOEs established in the form of public enterprises. It is suggested that it is necessary to revise the Law concerning the Suspension of Debt Payment Obligation (UU PKPU) that the party entitled to file a bankruptcy against SOEs engaged for the public benefits is the Minister of SOEs and it is also necessary to emphasize that the SOEs engaged for the public benefits, whose capital is entirely owned by the state and is not divided into shares, is in the form of public enterprises.